Exploring the innovative methods for evaluating educational efficiency - Haddad, Meryana Zuhair; Yee, Mei Heong; Abdul Razzaq, Abdul Rasid; Tee, Tze Kiong (2021)
The aim of this study is to provide information about educational efficiency by synthesizing existing literature, with an emphasis on techniques used to assess educational efficiency for the Decision-Making Unit (DMU). A thorough search of the existing literature was done using the terms ‘Education Efficiency,' ‘School Performance,' and ‘Efficiency Measurements' in the related systematic databases of ‘Web of Science' ‘Scopus,' and ‘Google Scholar'. The search yielded 1500 articles published between the years 2010 and 2021. The results indicate that nonparametric approaches Data Envelopment Analysis (DEA) and parametric approaches Stochastic Frontier Analysis (SFA) are the primary methodologies utilized in the literature to drive the most significant metrics of education efficiency, based on pre-determined inclusion measures and a theme evaluation. The results of this study are expected to provide important insights and advantages to education's key stakeholders. Aside from adding to the existing literature on educational efficiency, this study has the potential to inform ongoing educational changes taking place significantly and promptly throughout the world.